2018
DOI: 10.1186/s10397-018-1053-5
|View full text |Cite
|
Sign up to set email alerts
|

Didactic lectures versus simulation training: a randomised pilot evaluation of its impact on surgical skill

Abstract: Background: The Bristol enquiry and national surveys have highlighted medicolegal concerns, reduction in training time available for trainees and the change from trainees performing procedures for the first time on patients. The Royal Colleges have taken an active role in advocating the use of simulation training prior to doctors undertaking operative procedures in real time. This study compares didactic lecture-based teaching to simulation training using a quantitative assessment tool. Method: Randomised pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Most studies about SBL are observational evaluations of the learners' selfreported satisfaction with the simulation experience with no objective findings [4]. Acquisition of surgical skills through simulation training demonstrated to be superior to didactic lecture-based teaching in performing diagnostic laparoscopy [28], obstetrical emergencies [5,8], and medical ICU [25]. Moreover, the use of simulators in medical education has been examined in comparison with other traditional teaching methods, mainly didactic lectures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies about SBL are observational evaluations of the learners' selfreported satisfaction with the simulation experience with no objective findings [4]. Acquisition of surgical skills through simulation training demonstrated to be superior to didactic lecture-based teaching in performing diagnostic laparoscopy [28], obstetrical emergencies [5,8], and medical ICU [25]. Moreover, the use of simulators in medical education has been examined in comparison with other traditional teaching methods, mainly didactic lectures.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students should practice an enormous set of skills and training requirements to develop their clinical, interpersonal, and social proficiency. However, it is not accepted that trainees perform such procedures, for the first time, on patients [28]. Simulation-based medical education (SBME) has been proposed as an active training tool that bridges the gap between education and clinical practice [29].…”
Section: Introductionmentioning
confidence: 99%
“…19 Exposure to hands-on teaching using manikins promotes the theory of experiential learning and allows the participants an enhanced decision-making ability in the emergency scenario. 20 Repetitive practice through simulations followed by reflective observation with adequate debriefing that forms the hallmark of simulation-based education has proven to be a superior method in knowledge acquisition and retention, evident in this study too. 21…”
Section: Discussionmentioning
confidence: 70%
“…During the IPOS Ponseti casting workshops, only 40% of the training was hands-on while most of the section was conducting through lecture. This may be an issue as Supramaniam et al 41 demonstrated that hands-on simulation training is a superior training method compared with didactic lecturing on surgical skills. Our study's findings in association with the literature are being considered by the IPOS faculty as they continue to look to improve the IPOS casting workshop.…”
Section: Discussionmentioning
confidence: 99%